Suicide in the Context of Elite Sport: a Meta-Ethnographic Synthesis - Juliana Camilo; Jorge Correia Santana Almeida; Carolina Hamodi Galán (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Suicide or its attempts are a serious problem that has drawn the attention of different areas of knowledge related to the field of sports. However, in most cases, the analyses are based on psychopathological visions or physical trauma without understanding the particularities of mental health. The article presents a meta-ethnography review of the literature on qualitative research on suicide in athletes from 2012 to 2022. The topics addressed in the studies are diverse: the importance of healthy relationships, the visibility of mental health problems, the normalization of violence by coaches, and the lack of emotional support. It is essential for athletes to have a support network (including coaches, mental health professionals, etc.). The issues that have affected athletes identified with suicidal ideation include a prolonged combination of concussion symptoms, academic problems, normalized violent training practices, high demands, the invisibility of suffering, and exposure to traumatic events. It required training of teachers/coaches in mental health, social support during injury recovery, ongoing mental health education, close relationships between coaches and athletes, involvement of sports psychiatry/psychology specialists, support from the environment, and balance between performance and personal development.